Renin–Angiotensin System: An Important Player in the Pathogenesis of Acute Respiratory Distress Syndrome - Hrenak, Jaroslav; Simko, Fedor (International journal of molecular sciences, 2020)
Acute respiratory distress syndrome (ARDS) is characterized by massive inflammation, increased vascular permeability and pulmonary edema. Mortality due to ARDS remains very high and even in the case of survival, acute lung injury can lead to pulmonary fibrosis. The renin–angiotensin system (RAS) plays a significant role in these processes. The activities of RAS molecules are subject to dynamic changes in response to an injury. Initially, increased levels of angiotensin (Ang) II and des-Arg9-bradykinin (DABK), are necessary for an effective defense. Later, augmented angiotensin converting enzyme (ACE) 2 activity supposedly helps to attenuate inflammation. Appropriate ACE2 activity might be decisive in preventing immune-induced damage and ensuring tissue repair. ACE2 has been identified as a common target for different pathogens. Some Coronaviruses, including SARS-CoV-2, also use ACE2 to infiltrate the cells. A number of questions remain unresolved. The importance of ACE2 shedding, associated with the release of soluble ACE2 and ADAM17-mediated activation of tumor necrosis factor-α (TNF-α)-signaling is unclear. The roles of other non-classical RAS-associated molecules, e.g., alamandine, Ang A or Ang 1–9, also deserve attention. In addition, the impact of established RAS-inhibiting drugs on the pulmonary RAS is to be elucidated. The unfavorable prognosis of ARDS and the lack of effective treatment urge the search for novel therapeutic strategies. In the context of the ongoing SARS-CoV-2 pandemic and considering the involvement of humoral disbalance in the pathogenesis of ARDS, targeting the renin–angiotensin system and reducing the pathogen’s cell entry could be a promising therapeutic strategy in the struggle against COVID-19.